2014
DOI: 10.3928/1081597x-20140422-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Deformation Parameters After SMILE, LASEK, and Femtosecond Laser-Assisted LASIK

Abstract: Applanation time (applanation 1) and deformation amplitude (as measured with the CorVis ST tonometer) may be helpful in assessing corneal biomechanical changes after corneal refractive surgery. The relations between these parameters should be discussed in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 27 publications
5
70
0
Order By: Relevance
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences between the results in small-incision lenticule extraction and those in the other procedures. 71 It is conceivable but currently inconclusive that smallincision lenticule extraction may offer increased postoperative corneal biomechanical stability compared with LASIK.…”
Section: Corneal Biomechanical Strengthmentioning
confidence: 99%
“…In this case no mechanical difference can be expected. Also, in vivo measurements of corneal biomechanics after SmILE and LASIK surgery using air-puff deformation systems are inconclusive [11][12][13]17,33 potentially because they do not measure long-term deformation, which is essential for maintaining the corneal shape over time. In our experimental setting we applied the load gradually from the posterior surface and then measured its relaxation behavior under constant load.…”
Section: Discussionmentioning
confidence: 99%